"A highway to battlegrounds": Jewish territorialism and the State of Israel, 1945–1960. Issue 2 (3rd July 2019) - Almagor, Laura
ABSTRACT: This article explores the relationship between the Jewish Territorialist movement and the State of Israel during the first decade of the Jewish State's existence. Territorialism was never explicitly anti-Zionist, but it did grow increasingly critical of Zionist policies, especially regarding the Palestinian Arabs, and of Israel's militaristic character. While their stance vis-à-vis the young state became ever more negative, the Territorialists established contacts with members of the bi-nationalist Ihud movement. The fact that these "atypical" Zionists affiliated themselves with Territorialism during the 1950s demonstrates that May 1948 did not spell the end of alternative expressions of Jewish political behavior.